Internalization of Islamic Values in Developing Students' Actual Morals - Tambak, Syahraini; Hamzah, Hamzah; Sukenti, Desi; Sabdin, Mashitah (Jurnal Pendidikan Indonesia, 2021)
This study aims to explore the efforts of madrasah teachers to internalize Islamic values in developing students' actual morals. Using case study research by conducting in-depth interviews with 8 madrasah tsanawiyah teachers and analyzing them with data cleaning, transcripts, coding and categorization, and interpretation. This research resulted in: First, duha sunnah and fardhu prayer in congregation, and get used to respect the teacher, to manage the syahwiya power of students, resulting in "iffah" which gave birth to the morals of jud, syakha', qana'ah, amanah, zuhud, rahmah, hilm, and al-afwu. Second, get used to dzikrullah, and accustom shiyam sunnah, to curb the hammiya power of students, resulting syaja'ah, ‘adalah, ihsan, insyaf, rahmah, and hilm. Third, get used to muhadharah activities, and Islamic integrative learning, to educate students' powers of mufakkara, thus giving birth to wisdom and fathanah behavior. It can be concluded that the internalization of Islamic values in developing students' actual morals is duha sunnah and fardhu prayer in congregation, get used to respect the teacher, get used to dzikrullah, accustom shiyam sunnah, muhadharah activity, and Islamic integrative learning, to curb the spiritual power of shahwiya, manage power of hammiya, and educating students powers of mufakkara, thus giving birth to the behavior of' iffah, jud, syakha', qana'ah, amanah, zuhud, rahmah, hilm, al-afwu, syaja'ah, 'adalah, ihsan, insyaf, mujahadah, sabr, wisdom, and fathanah. The results of this study have implications for the theory of "Islamic moral development" which can be applied to all madrasah education in Indonesia and the Islamic world.